A rare case of a 2-pound urinary bladder stone in a 32-year-Old male - Aalamnoor Singh Pannu; Barinder Singh Pannu (Urology Case Reports, 2025)
Giant bladder stones over 500 g are extremely rare. This case report describes a 2-pound bladder stone, emphasizing its clinical presentation, diagnostic challenges and surgical management.We present a case of a 32-year-old male with progressive urinary retention, hematuria, and dysuria. Imaging revealed a 2-pound bladder calculus, managed successfully via open suprapubic cystolithotomy. The patient's symptoms resolved completely, and recovery was uneventful.This case highlights the need for early diagnosis and timely surgical management to prevent complications such as obstruction and renal damage. Preventive measures, including adequate hydration and nutrition, remain vital, especially in resource-limited settings.